Design and analysis of coronary stent. (7th September 2011) - Ravikumar, P.; Bharathiraja, E.; Tharani, V.; Yamuna, R.; Yamunarani, T.
Intravascular stents of various designs are currently in use to restore patency in atherosclerotic coronary arteries and it has been found that different stents have different in-stent restenosis rates. Computational studies are used to investigate the mechanical behaviour of stents by means of strength and temperature analysis. In this paper, we test the hypothesis that two different stent designs (S7 and Cypher). An analysis of the arterial wall stresses in the stented arteries indicates that the S7 (modular) stent design causes lower stress to an atherosclerotic vessel with a localised stenotic lesion compared to the Cypher stent design.